Energy Technology 2014 carbon dioxide management and other technologies : Proceedings of a symposium, Energy Technologies and Carbon Dioxide Management, sponsored by the Energy Committee of the Extraction & Processing Division and the Light Metals Division of The Minerals, Metals & Materials Society (TMS) with papers contributed by two symposia, High-temperature Material Systems for Energy Conversion and Storage and Solar Cell Silicon, sponsored by the Energy Conversion and Storage Committee of the Electronic, Magnetic & Photonic Materials Division of The Minerals, Metals & Materials Society (TMS) held during TMS 2014 143rd Annual Meeting & Exhibition, February 16-20, 2014 San Diego Convention Center San Diego, California, USA. - Wang, Cong (Engineer) (John Wiley & Sons, Inc., 2014)
This book addresses the issues, intricacies, and challenges relating to energy and environmental sciences. Papers cover various technological aspects of sustainable energy eco-systems and processes that improve energy efficiency, and reduce and sequestrate carbon dioxide (CO2) and other greenhouse emissions. The collection also emphasizes the need for sustainable technologies in extractive metallurgy, materials processing and manufacturing industries with reduced energy consumption and CO2 emission. Industrial energy efficient technologies include innovative ore beneficia.
Includes indexes.
Keywords: Power resources -- Congresses.; elektronické knihy; electronic books